3‐Hydroxy‐3‐methylglutaryl coenzyme A reductase inhibitor (fluvastatin) decreases inflammatory angiogenesis in mice. Issue 5 (24th November 2012) - Araújo, Fernanda A.; Rocha, Monaliza A.; Capettini, Luciano S. A.; Campos, Paula P.; Ferreira, Mônica A. N. D.; Lemos, Virginia S.; Andrade, Silvia P.
<x xml:space="preserve">Abstract</x> Statins, 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase inhibitors, have been shown to ameliorate a number of vascular diseases. We evaluated the inflammatory and angiogenic components of the fibrovascular tissue induced by subcutaneous implants in mice and their modulation by fluvastatin. Our results showed that the statin (0.6 and 6 mg/kg/day) inhibited hemoglobin (Hb) content (51%) and vascular endothelial growth factor (VEGF) levels (71%) in the treated group compared with the control group. The inflammatory component, as assessed by N‐acetyl‐β‐D‐glucosaminidase activity and tumor necrosis factor‐α (TNF‐α) level was also decreased by the compound. In the treated group; the inhibition of the enzyme activity was 33% and the cytokine was 67% relative to the control. In these implants the statin was also able to decrease nitric oxide (NO) production, detected with an NO‐sensitive electrode. To our knowledge this is the first study demonstrating an inhibitory role of fluvastatin on the production of NO in inflammatory angiogenesis of newly formed fibrovascular tissue.